Upaya Guru Pak Meningkatkan Antusias Peserta Didik Sekolah Dasar (Sd) Dalam Mengerjakan Tugas Dengan Menggunakan Model Project - Lius Ade Boy Nazara; Riste Tioma Silaen (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2023)
PAK learning activities at the elementary school level always have their own challenges. Basically PAK emphasizes Christian values, one of which is responsibility in doing the assignments given by the teacher to students. Ongoing learning and giving assignments Students often neglect responsibility for doing it, students are more enthusiastic about working on other subject assignments compared to PAK, even students prioritize other subject assignments because they feel happy compared to PAK assignments, so that assignments from PAK are set aside because assignments PAK only uses theory that is considered normal. This situation is centered on the teacher which tends to make the learning process less than optimal. Therefore, the purpose of writing this article is to describe a fun PAK learning process using a project model so that students are more enthusiastic about doing PAK assignments that are more weighty and of high value.